The Polyketide Pks1 Contributes to Biofilm Formation in Mycobacterium tuberculosis - Pang, Jennifer M. (American Society for Microbiology, 2012)
Infections caused by biofilms are abundant and highly persistent, displaying phenotypic resistance to high concentrations of antimicrobials and modulating host immune systems. Tuberculosis (TB), caused by Mycobacterium tuberculosis, shares these qualities with biofilm infections. To identify genetic determinants of biofilm formation in M. tuberculosis, we performed a small-scale transposon screen using an in vitro pellicle biofilm assay. We identified five M. tuberculosis mutants that were reproducibly attenuated for biofilm production relative to that of the parent strain H37Rv. One of the most attenuated mutants is interrupted in pks1, a polyketide synthase gene. When fused with pks15, as in some M. tuberculosis isolates, pks1 contributes to synthesis of the immunomodulatory phenolic glycolipids (PGLs). However, in strains such as H37Rv with split pks15 and pks1 loci, PGL is not produced and pks1 has no previously defined role. We showed that pks1 complementation restores biofilm production independently of the known role of pks1 in PGL synthesis. We also assessed the relationship among biofilm formation, the pks15/1 genotype, and M. tuberculosis phylogeography. A global survey of M. tuberculosis clinical isolates revealed surprising sequence variability in the pks15/1 locus and substantial variation in biofilm phenotypes. Our studies identify novel M. tuberculosis genes that contribute to biofilm production, including pks1. In addition, we find that the ability to make pellicle biofilms is common among M. tuberculosis isolates from throughout the world, suggesting that this trait is relevant to TB propagation or persistence.